The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pcbi.1008987
|View full text |Cite
|
Sign up to set email alerts
|

Targeted modification of the Per2 clock gene alters circadian function in mPer2luciferase (mPer2Luc) mice

Abstract: Modification of the Per2 clock gene in mPer2Luc reporter mice significantly alters circadian function. Behavioral period in constant dark is lengthened, and dissociates into two distinct components in constant light. Rhythms exhibit increased bimodality, enhanced phase resetting to light pulses, and altered entrainment to scheduled feeding. Mechanistic mathematical modelling predicts that enhanced protein interactions with the modified mPER2 C-terminus, combined with differential clock regulation among SCN sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…S6A and S6B, see also Ralph et al, 2021). Male mPer2 Luc mice have been reported to display a greater predisposition to display bimodal locomotor rhythms relative to male C57Bl/6 mice (Ralph et al, 2021), but we did not observe a difference in the duration of the nightly siesta in male mice from each line (Suppl. Fig.…”
Section: Discussionmentioning
confidence: 86%
“…S6A and S6B, see also Ralph et al, 2021). Male mPer2 Luc mice have been reported to display a greater predisposition to display bimodal locomotor rhythms relative to male C57Bl/6 mice (Ralph et al, 2021), but we did not observe a difference in the duration of the nightly siesta in male mice from each line (Suppl. Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Mice homozygous for a targeted allele of Dbp have only a modest circadian phenotype (Lopez-Molina et al, 1997). Homozygotes of both the Per2 LucSV and Per2 Luciferase lines have altered circadian rhythms (Ralph et al, 2021; Yoo et al, 2017; see below). The GFP-expressing Dbp transcript lacks the native 3′ UTR and uses an exogenous polyadenylation sequence, which could affect Dbp gene expression and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of a single Per2 LucSV allele (as used in our studies) on period length has not been reported, but this could contribute to the longer period of Per2 LucSV/+ explants, relative to Dbp Luc/+ explants. Interestingly, Ralph et al (2021) recently reported that the Per2 Luciferase reporter that uses the endogenous Per2 3′UTR (Yoo et al, 2004) also has longer period in DD and other circadian phenotypes. Tosini and colleagues have also recently reported retinal degeneration and alterations in classical photoreception in aged male Per2 Luciferase/Luciferase mice (Goyal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For organotypic SCN slice culture from heterozygous PER2::LUC knock-in mice (Yoo et al, 2004), 2-4 months old mice were used in VIP application experiments and P11-14 mice were used in optogenetic stimulation experiments. We used heterozygous PER2::LUC mice as the PER2::LUC knock-in allele can alter circadian functions such as free-running period (Ralph et al, 2021). All animals were housed in a 12:12 light-dark cycle (except as noted), and had food and water provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%